Pengaruh Degree of Availability (DOA) Urea (CO(NH2)2) Sebagai Sumber Nitrogen pada Proses Pack Nitriding terhadap Sifat Fisik dan Mekanik Sprocket Non Pabrikan Resmi - Purwaningrum, Yustiasih; Yudhawan, M. Riza; Rahman, A. (TURBO [Tulisan Riset Berbasis Online], 2025)
The aimed of this experimen is to determine the effect of degree of availability (DOA) variation of urea as a source of nitrogen in the pack nitriding process on the physical and mechanical properties of sprockets that manufactured from non-official motorcycle manufacturer.  The DOA variation used is 0.1 gr/mm2; 0.15 gr/mm2; and 0.2 gr/mm2. The pack nitriding process is carried out using a temperature of 550°C, a holding time of 2.5 hours and a cooling process with water medium. The testing process carried out is chemical composition, wear, hardness, observation of microstructure and corrosion rate. The results of the chemical composition test showed that the nitrogen content of all DOA variations of the nitriding pack increased compared to before the pack nitriding process. The amount of nitrogen from pack nitriding with DOA variation were 0.1336 %  for 0.1 gr/mm2;  0.1938 % to 0.15 gr/mm2; and 0.1996 % for 0.2 gr/mm2. While non-official manufacturer sprockets have a nitrogen content of 0.0004%. The wear value of the nitriding pack is smaller than before the nitriding pack. The lowest wear value was found in the nitriding pack result with a DOA of 0.2 gr/mm2, which was 0.00011 mm3/kg.m. This value shows that the nitriding pack has more wear resistance compared to the initial material which has a value of 0.00059 mm3/kg.m. The pack nitriding process can also increase the hardness value. The hardness value of the sprocket before the nitriding process is 266.67 VHN. The results of pack nitriding showed that the highest hardness value was found in the DOA variation of 0.2 gr/mm2 with a value of 356.18 VHN, followed by DOA 0.15 gr/mm2 with a value of 315.11 VHN and the lowest value was found in DOA 0.1 gr/mm2 with a value of 267.67 VHN. The results of corrosion testing show that all specimens before and after the nitriding process can be categorized as having excellent corrosion resistance.